The impacts of plant physiological responses to rising CO2 on humidity-based extreme heat - Ashley E. Cornish; Gabriel J. Kooperman; Andrew J. Grundstein; Christopher B. Skinner; Abigail L. S. Swann (npj Climate and Atmospheric Science)
Abstract Plant physiological responses to rising CO2 have been shown to contribute to increasing extreme heat; but their impacts on co-occurrences of high heat and humidity have not been assessed previously. Since heat stress depends on both, reductions in evapotranspiration and increases in sensible heat can incite competing influences on co-occurrence metrics (e.g., heat index). Here we analyze plant physiological forcing in idealized simulations that isolate plant physiological from radiative impacts of rising CO2. Our results demonstrate that increasing temperature has a larger influence than declining moisture, leading to overall CMIP6 multi-model mean heat index increases. Model differences are driven by varying levels of transpiration decline, which can be partially offset by leaf-area-driven increases in canopy evaporation in some models/regions; as highlighted by differences between two versions of one model (CESM) with high and low levels of leaf-area change. This analysis helps clarify the role of plants in future climate and human health.